X-Ray Polarization Detection of Cassiopeia A with IXPE - Vink Jacco; Prokhorov Dmitry; Ferrazzoli Riccardo; Slane Patrick; Zhou Ping; Asakura Kazunori; Baldini Luca; Bucciantini Niccoló; Costa Enrico; Di Marco Alessandro; Heyl Jeremy; Marin Frédéric; et al. (IOP Publishing Ltd, 2022)
We report on a similar to 5 sigma detection of polarized 3-6 keV X-ray emission from the supernova remnant Cassiopeia A (Cas A) with the Imaging X-ray Polarimetry Explorer (IXPE). The overall polarization degree of 1.8% +/- 0.3% is detected by summing over a large region, assuming circular symmetry for the polarization vectors. The measurements imply an average polarization degree for the synchrotron component of similar to 2.5%, and close to 5% for the X-ray synchrotron-dominated forward shock region. These numbers are based on an assessment of the thermal and nonthermal radiation contributions, for which we used a detailed spatial-spectral model based on Chandra X-ray data. A pixel-by-pixel search for polarization provides a few tentative detections from discrete regions at the similar to 3 sigma confidence level. Given the number of pixels, the significance is insufficient to claim a detection for individual pixels, but implies considerable turbulence on scales smaller than the angular resolution. Cas A's X-ray continuum emission is dominated by synchrotron radiation from regions within less than or similar to 10(17) cm of the forward and reverse shocks. We find that (i) the measured polarization angle corresponds to a radially oriented magnetic field, similar to what has been inferred from radio observations; (ii) the X-ray polarization degree is lower than in the radio band (similar to 5%). Since shock compression should impose a tangential magnetic-field structure, the IXPE results imply that magnetic fields are reoriented within similar to 10(17) cm of the shock. If the magnetic-field alignment is due to locally enhanced acceleration near quasi-parallel shocks, the preferred X-ray polarization angle suggests a size of 3 x 10(16) cm for cells with radial magnetic fields.